A discussion about quantum black holes - Soares, Matheus S.; Menezes, Gabriel (Cadernos de Astronomia, 2023)
In this work we will discuss the main physical aspects related to the process of particle creation by black holes. To this end, we will briefly examine the formalism of quantum field theory in curved spacetime. We will discuss why we should use this approach and how it is employed to study quantum processes in the vicinity of the event horizon of a black hole. We will also present results that reveal how black holes can play a key role in the search for a theory of quantum gravity.